Effects of a national checklist on recommended procedures among patients with type 2 diabetes - Øyvind Snilsberg; Tor Iversen; Anne Karen Jenum; Yuting Zhang (BMC Health Services Research)
Abstract Background Type 2 diabetes (T2D) is a common, potentially disabling, and costly chronic condition that requires consistent management. In 2008, Norway introduced a national checklist outlining services to include in an annual T2D exam, along with a reimbursement code for general practitioners (GPs) to bill upon completing it. This study investigates whether GP adoption of the checklist improves adherence to recommended services for T2D patients. Methods To investigate the impact of GP checklist adoption, we use Norwegian registry data from 2006 to 2021 and apply two difference-in-differences (DID) methods that account for staggered adoption timing: the two-way fixed effects (TWFE) estimator and Callaway and Sant’Anna’s DID method for variation in exposure timing (CSDID) (Callaway B. et al., J Econom 225:200–30, 2021). Results We find that installing the electronic form has modest effects on the use of some recommended procedures. Conclusions Our study suggests that using the electronic form can have a positive effect on recommended services. However, the modest impact indicates that installing the form does not necessarily translate into its active regular use.